2021
DOI: 10.3390/s21248265
|View full text |Cite
|
Sign up to set email alerts
|

Development of 3D MRI-Based Anatomically Realistic Models of Breast Tissues and Tumours for Microwave Imaging Diagnosis

Abstract: Breast cancer diagnosis using radar-based medical MicroWave Imaging (MWI) has been studied in recent years. Realistic numerical and physical models of the breast are needed for simulation and experimental testing of MWI prototypes. We aim to provide the scientific community with an online repository of multiple accurate realistic breast tissue models derived from Magnetic Resonance Imaging (MRI), including benign and malignant tumours. Such models are suitable for 3D printing, leveraging experimental MWI testi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Region growing [53] and Hoshen-Kopelman [54] algorithms were applied to pre-processed subtraction images from the DCE-fl3D sequence for tumor segmentation. Details regarding breast model processing are described in [55].…”
Section: Model Processingmentioning
confidence: 99%
See 1 more Smart Citation
“…Region growing [53] and Hoshen-Kopelman [54] algorithms were applied to pre-processed subtraction images from the DCE-fl3D sequence for tumor segmentation. Details regarding breast model processing are described in [55].…”
Section: Model Processingmentioning
confidence: 99%
“…This repository includes the model files, allowing an easy reconfiguration of breast tissue models, if required; and an executable file enabling the generation of models that incorporate the dielectric properties of tissues for a chosen frequency value within the range of 3-10 GHz (with a step of 0.01 GHz), which fits investigators' needs and all developmental stages of any MWI prototype system. The developed repository can be accessed in [46].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the dielectric characteristics of malignant and healthy breast tissue at microwave frequencies, MWI devices have been researched in recent years for early-stage breast cancer diagnostics [ 6 , 7 , 8 ]. Cancerous tissue differs from healthy tissue because the permeability of the cancer cell membrane changes, allowing more water to pass into the cell [ 9 ]. As a result, malignant cells have more water and dissolved ions inside them with respect to healthy cells of exactly the same type of tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Microwave imaging has been used in medical applications, including the imaging of breast cancer [ 19 ], axillary lymph nodes [ 20 , 21 , 22 ], brain strokes [ 23 , 24 ] and bones [ 25 ]. These medical applications have justified the study of dielectric properties of many biological tissues, including liver [ 26 ], breast [ 27 , 28 ] among many others [ 29 , 30 ], and have triggered classification based studies [ 31 , 32 , 33 , 34 , 35 , 36 ]. Experimental work carried out in the field of dentistry has shown that frequencies in the microwave/millimetre-wave range are able to discriminate between healthy teeth and teeth with visible caries [ 37 , 38 ], which motivates further investigation of microwave diagnostics applicability in detecting healthy teeth and teeth affected by caries.…”
Section: Introductionmentioning
confidence: 99%